Indonesia : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Indonesia. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses key issues related to the Indonesian economy. Indonesia has weathered challenging economic conditions well. The economy has safely navigated the commodity price shocks, tightening financial conditions, and repeated bouts of turbulence in global financial markets, assisted by broadly appropriate macroeconomic policies. The Indonesian economy, however, is still facing headwinds. Against this backdrop, the 2015 Article IV consultation is focused on the need to manage short-term vulnerabilities and to boost potential growth in the medium-term. The challenge for Indonesia will be to follow through on the reforms that the government has already launched and undertake further macrocritical reforms to boost productivity and diversify growth, while maintaining macroeconomic and financial stability.